KONFLIK KELAS SOSIAL DALAM NOVEL ORANG-ORANG PULAU KARYA GIYAN - Putri, Liziana; Juita, Novia; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This research aims to describe the form of social class, the causes of social class conflict, and the impact of social class conflict in novel Orang-orang Pulau by Giyan. Data in this research are sentences, direct speeches of characters and author narratives that can be interpreted as social class. Source of data in this research is novel Orang-orang Pulau by Giyan which published for the first time by Beranda in December 2013. This research is a qualitative research and using descriptive analysis method. Based on the results of this research, it can be concluded that the social indicators in novel Orang-orang Pulau by Giyan are: (1) the form of social class, it can be seen in terms of economi, ie upper class, middle class, lower class. In terms of social status, ie upper class, middle class, lower class. And in terms of political status, ie upper class, middle class, and lower class; (2) the causes of social class conflict because of social change, there are differences in cultural patterns, and there are differences in social status that leads to rebellion between upper and lower classes; And (3) the impact of social class conflict, ie strengthened sense of solidarity group, the destruction of groups, loss of property and human sacrifice, the destruction of existing values and social norms, and the change of individual personality.Keywords: social class, conflict, and the causes of conflict